Brief Report: Interleukin‐38 Exerts Antiinflammatory Functions and Is Associated With Disease Activity in Systemic Lupus Erythematosus. Issue 12 (25th November 2015) - Rudloff, Ina; Godsell, Jack; Nold‐Petry, Claudia A.; Harris, James; Hoi, Alberta; Morand, Eric F.; Nold, Marcel F.
Abstract : Objective: Knowledge of interleukin‐38 (IL‐38), formerly IL‐1 family member 10, is sparse, but Il1f10 polymorphisms are associated with inflammatory diseases, and recombinant IL‐38 inhibits inflammatory responses similar to those reported in the context of systemic lupus erythematosus (SLE). We undertook this study to explore the function of endogenous IL‐38 in human peripheral blood mononuclear cells (PBMCs) as well as its abundance in serum in a well‐characterized cohort of SLE patients. Methods: Serum IL‐38 and IL‐10 levels were quantified by enzyme‐linked immunosorbent assay in 142 SLE patients at ≤3 consecutive visits and in 28 healthy volunteers. To assess IL‐38 function, we silenced IL‐38 in PBMCs from healthy donors using IL‐38 small interfering RNA (siRNA). Results: IL‐38 (63–5, 928 pg/ml) was detectable in 16% of 372 serum samples. IL‐38 abundance was significantly higher in samples from SLE patients than in samples from healthy controls ( P = 0.004) and 11‐fold higher in patients with active disease (SLE Disease Activity Index 2000 [SLEDAI‐2K] score of ≥4) than in those with inactive disease (SLEDAI‐2K score of <4) ( P = 0.044). Importantly, IL‐38 detection was associated with increased risk of renal lupus (relative risk [RR] 1.6, P = 0.027) and central nervous system lupus (RR 2.3, P = 0.034), and detectable baseline IL‐38 entailed a 1.6‐fold increased risk of subsequently meeting criteria for persistently active disease ( P = 0.0097). Longitudinal time‐adjusted mean IL‐38 concentration was also 6‐fold higher in patients with persistently active disease than in those without ( P = 0.023). Remarkably, PBMCs treated with IL‐38 siRNA produced up to 28‐fold more of the proinflammatory mediators IL‐6, CCL2, and APRIL than did control siRNA–transfected cells upon stimulation with Toll‐like receptor agonists. Similarly, in SLE patients, the antiinflammatory cytokine IL‐10 was 5‐fold more abundant when IL‐38 was detectable. Conclusion: This is the first study of the function of endogenous IL‐38, and the data suggest that IL‐38 may be protective in SLE. A strong association between IL‐38 and SLE severity suggests that IL‐38 expression is driven by processes linked to SLE pathogenesis. Exploitation of the regulatory effects of IL‐38 may represent a promising therapeutic strategy in SLE.